Kekuatan Tegangan Kompresi Pada Konstruksi Kapal Pompong Berbahan Dasar Plastik High Density Polyethylene - Jamal (Politeknik Negeri Madura, 2018)
The Pompong ship is traditional small boats that operates using a machine housed inside a ship's body or an inboard motor. The word term is known by the people around the waters of the Straits of Melaka especially in the waters of coastal Riau. The need for pompong ships around the coastal waters of Riau at this time is very much and is generally used for cargo boats, passenger boats and fishing boats. Nevertheless, the basic material of shipbuilding pompong at this time more difficult and more expensive so that need new breakthrough material of material substitution, in this research is used plastic material High Density Polyethylene (HDPE) as shipbuilding of Pompong. This research is a follow-up research from my previous research which started from choosing ship models, material strength analysis by material test, velocity calculation of ship construction until tensile strength analysis of ship construction using finite element method (FEM) analysis. While the compression strength analysis of vessel compression has not been calculated so that this study. In this research Three models have been done to verify the strength of ship construction using finite element method (FEM) analysis. Of the three models, the biggest stresses occur in the inner bottom plate of the capture gear space under Load case 1 condition and load case condition. Load case 1 is empty fish loading condition, 100% net load and 100% fuel while the case load 3 is on when 100% full charge, 100% net load and 10% fuel. The largest compression strength is 15.82 MPa in all load cases with safety factor of 1.26 against the standard given rule class.